2018
DOI: 10.4314/ahs.v17i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal malignancies at five regional referral hospitals in Uganda

Abstract: BackgroundThere is a paucity of published data regarding the trend and distribution of gastrointestinal malignancies in Uganda.ObjectivesTo study the trend and distribution of gastrointestinal malignancies over a 10 year period at five regional referral hospitals in Uganda.MethodsPatient's charts with histologically confirmed diagnoses of gastrointestinal malignancies for the period 2002–2011 were identified. Case information, which included age at diagnosis, sex, and year of diagnosis, primary anatomic site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Smoking was present in 70% 0f patients [14]. Obayo et al, (2017) found that median age was 53.9 years, esophageal cancer was the most common (28.8%) followed by liver (25.8%), stomach (18.4%) and colorectal (14.3%). Hepatitis B was prevalent in most patients with HCC and Helicobacter pylori was present in 70% of gastric tumors [15].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was present in 70% 0f patients [14]. Obayo et al, (2017) found that median age was 53.9 years, esophageal cancer was the most common (28.8%) followed by liver (25.8%), stomach (18.4%) and colorectal (14.3%). Hepatitis B was prevalent in most patients with HCC and Helicobacter pylori was present in 70% of gastric tumors [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors in Sub-Saharan Africa observed an increase in the incidence of CRC which may be due to an actual increase or due to greater awareness to present to hospital with signs and symptoms of CRC in our patient population, increased specialist referrals to hospital or a better reputation for CRC management in our hospitals. More hospital admissions have been registered in Referral Hospitals in Central Uganda in the last 10 years however a higher rise in CRC has been observed [6]. The increasing prevalence and incidence of CRC is part of an on-going epidemiological shift in Sub-Saharan Africa with a rising burden from noncommunicable diseases to a reduction in burden from infectious communicable diseases [7,8].…”
Section: Possible Reasons Behind the Rise In Incidence Of Crc In Ugandamentioning
confidence: 99%
“…In gastrointestinal cancers, esophageal cancer is the commonest gastrointestinal malignancies (GIM), accounting for 28.8% [ 52 ]. Esophageal squamous cell carcinoma (ESCC) is most prevalent (98%) phenotype of esophageal cancer in Uganda [ 53 ].…”
Section: Findings Of the Reviewed Studiesmentioning
confidence: 99%